rdHSV-CA8 non-opioid analgesic gene therapy decreases somatosensory neuronal excitability by activating Kv7 voltage-gated potassium channels - Kandel, Munal B.; Zhuang, Gerald Z.; Goins, William F.; Marzulli, Marco; Zhang, Mingdi; Glorioso, Joseph C.; Kang, Yuan; Levitt, Alexandra E.; Kwok, Wai-Meng; Levitt, Roy C.; Sarantopoulos, Konstantinos D. (Frontiers in Molecular Neuroscience, 2024)
Chronic pain is common and inadequately treated, making the development of safe and effective analgesics a high priority. Osteoarthritis (OA), including knee OA, is a primary cause of chronic pain and disability worldwide and a significant contributor to loss of quality-adjusted life-years. Our previous data indicate that carbonic anhydrase-8 (CA8) expression in dorsal root ganglia (DRG) mediates analgesia via inhibition of neuronal ER inositol trisphosphate receptor-1 (ITPR1) via subsequent decrease in ER calcium release and reduction of cytoplasmic free calcium, essential to the regulation of neuronal excitability. This study tested the hypothesis that novel JDNI8 replication-defective herpes simplex-1 viral vectors (rdHSV) carrying a CA8 transgene (vHCA8) reduce primary afferent neuronal excitability. Whole-cell current clamp recordings in small DRG neurons showed that vHCA8 transduction caused prolongation of their afterhyperpolarization (AHP), an essential regulator of neuronal excitability. This AHP prolongation was completely reversed by the specific Kv7 channel inhibitor XE-991. Voltage clamp recordings indicate an effect via Kv7 channels in vHCA8-infected small DRG neurons.These data demonstrate for the first time that vHCA8 produces Kv7 channel activation, which decreases neuronal excitability in nociceptors. This suppression of excitability may translate in vivo as non-opioid dependent behavioral-or clinical analgesia, if proven behaviorally and clinically.